Pengaruh Bimbingan Orang Tua Terhadap Keberhasilan Pembelajaran Daring Siswa Kelas V SD Swasta Alwashliyah Dagang Krawan - Kartika Dewi; Hendra (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2022)
This research was motivated by the government's policy to carry out learning from home as a form of preventing the transmission of the covid-19 virus. Judging from the results of observations there are still students who do not collect assignments, are not active during online learning, are late in collecting assignments and there are also students who get low scores. This study aims to determine the effect of parental guidance on the success of student learning in learning from home at SD Swasta Alwashliyah Dagang Krawan. This type of research is descriptive research with a quantitative approach. The data collection technique was carried out by the method of observation, questionnaires and documentation. For data analysis used is a simple linear regression test. The results showed that there was an effect of parental guidance on the success of student learning in learning from home at SD Swasta Alwashliyah Dagang Krawan Village, seen through a simple linear regression equation Y = 29.8 + 0.395X, which means that if there is an increase in one variable X, the value of the Y variable will increase. of 0.395. Based on the results of data analysis using t-test, it is obtained tcount = 3.056 and ttable = 1.676 with a significant level of 5%, then the value of tcount > ttable is (3.056 > 1.676), so it can be concluded that Ha is accepted and Ho is rejected. Judging from the calculation of the coefficient of determination, parental guidance affects the success of student learning in learning from home by 16%, while 84% is influenced by other variables not included in this study.